International Financial Management, 14th Edition - Jeff Madura (Cengage Learning, 2020)
Gain an understanding of theory and practical insights you need for success in international finance today with Madura's best-selling INTERNATIONAL FINANCIAL MANAGEMENT, 14E. This reader-friendly approach builds on the fundamental principles of corporate finance to provide timely information and the understanding of managerial topics in a global environment necessary to prosper in international business. Clear explanations help you fully understand the important role of multinational corporations in global commerce. New content explores tradeoffs in international trade policies, the realities behind popular theories, multinational capital budgeting, barriers to entry in international markets, and the most recent changes internationally. Numerous examples, self-tests, hands-on exercises, and memorable real-world examples help you develop the skills and understanding necessary to perform at your best in international finance today. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.